Technical Perspective: Transactional Memory in the Operating System. - Moir, Mark (Communications of the ACM, 2008)
The article discusses computer applications that can successfully and simultaneously operate on multiple cores, examining the role of an operating system's transactional memory (TM) in managing complex operations. Programmers must coordinate tasks that can be operated in parallel and ensure that bottlenecks are avoided. Topics include locks used to ensure that critical sections of code operate atomically and avoiding synchronization bottlenecks. Also discussed is the combination of runtime libraries and compiler support.